2005
DOI: 10.1055/s-2005-836784
|View full text |Cite
|
Sign up to set email alerts
|

Eine vergleichende Untersuchung der Versorgung instabiler per- und intertrochantärer Femurfrakturen mittels DHS-Osteosynthese unter Verwendung der Trochanterabstützplatte und dem Proximalen Femurnagel (PFN)

Abstract: The aim of the present paper is to compare the results obtained using two osteosynthesis systems developed for the surgical treatment of unstable fractures of the trochanteric region of the femur: the proximal femoral nail (PFN) and the dynamic hip screw (DHS) with trochanteric butt-press plate (TBPP). From December 1997 to November 2000, 173 patients with instable trochanteric fractures (type 31 A-2 and A-3 according to the AO-classification) had osteosynthesis by PFN (n = 122) or DHS/TBPP (n = 51). The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…When comparing the union time for unstable fractures individually, it was shown that group 2 had a superior fracture union time (15.11 ± 3.98 weeks) compared to group 1. This study was similar to the studies conducted by Herode et al and Klinger et al [ 20 , 21 ]. The functional result of patients treated with PFN was marginally superior to that of patients treated with DHS; however, this difference was not statistically significant (p = 0.13).…”
Section: Discussionsupporting
confidence: 92%
“…When comparing the union time for unstable fractures individually, it was shown that group 2 had a superior fracture union time (15.11 ± 3.98 weeks) compared to group 1. This study was similar to the studies conducted by Herode et al and Klinger et al [ 20 , 21 ]. The functional result of patients treated with PFN was marginally superior to that of patients treated with DHS; however, this difference was not statistically significant (p = 0.13).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that even in complex fractures, fixation with DHS/TSP can be a more efficient procedure than fixation with IMN. When comparing this to results in the literature, we found that there were mixed results with some studies obtaining similar results [ 9 ], and others suggesting that IMN had shorter operating times [ 10 , 14 , 15 ], or no significant difference in operating time [ 16 ]. Whilst a small fraction of our patients received the short-stem IMN, their average operation time was marginally longer than the DHS/TSP procedure (89 vs 86 min); however, the cohort size is too small (8 patients) to make adequate assessment of the length of the short-stem IMN operation.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, from a surgical perspective, the DHS/TSP seems favourable in these complex, unstable fractures [ 9 ]. However, results in German populations contradict this, without reporting any functional difference between these two groups [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…PFN A ™ ,G a m m a 3 ™ etc.) zu empfehlen, da die zitierten Studien zu instabilen Frakturen hauptsächlich den PFN oder gar den Standard-Gamma-Nagel mit den bekannt hohen Komplikationsraten verwendeten[1,8,10,20,21,23,24,30,31]. Eine entsprechende Studie ist in unserer Klinik in Arbeit.…”
unclassified